2022
DOI: 10.1177/02761467221116294
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Adoption of Slow Fashion – An Exploratory Study of Multiple Stakeholders

Abstract: The growing consumer consciousness is accelerating the interest in sustainable products that offer better value and longevity. Slow fashion is one such philosophy that aims to provide meaningful and sustainable products advocating the needs of stakeholders. In this exploratory study, we find the barriers and support mechanisms affecting the adoption of slow fashion, specifically Indian handloom. The handloom industry is gradually depleting, posing challenges for stakeholders in the value chain. Though the exta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…In presenting a sustainability-focused business case for slow fashion, Presley and Meade (2018) highlighted a 2015 Global Corporate Sustainability report by Nielson suggesting that "73% of millennials are willing to spend more on a product if it comes from an ethical or sustainable brand." A growing body of empirical work surveys consumers' perspectives relating to slow fashion (de Lira and da Costa, 2022;de Oliveira et al, 2022), as well as those from producers and related stakeholders (Chhabra et al, 2022;Sellitto et al, 2022;Hall, 2018). Sun et al ( 2021) emphasized "product durability, an important and valued dimension of sustainable consumption," but also highlight that consumers appear to suffer from "durability neglect, a failure to consider how long a product will last."…”
Section: Slow Versus Fast Fashionmentioning
confidence: 99%
See 1 more Smart Citation
“…In presenting a sustainability-focused business case for slow fashion, Presley and Meade (2018) highlighted a 2015 Global Corporate Sustainability report by Nielson suggesting that "73% of millennials are willing to spend more on a product if it comes from an ethical or sustainable brand." A growing body of empirical work surveys consumers' perspectives relating to slow fashion (de Lira and da Costa, 2022;de Oliveira et al, 2022), as well as those from producers and related stakeholders (Chhabra et al, 2022;Sellitto et al, 2022;Hall, 2018). Sun et al ( 2021) emphasized "product durability, an important and valued dimension of sustainable consumption," but also highlight that consumers appear to suffer from "durability neglect, a failure to consider how long a product will last."…”
Section: Slow Versus Fast Fashionmentioning
confidence: 99%
“…Relating to product durability, the term “slow fashion” is often used to describe a movement towards producing longer-lasting products that consumers dispose of less quickly (Jung and Jin, 2014). In presenting a sustainability-focused business case for slow fashion, Presley and Meade (2018) highlighted a 2015 Global Corporate Sustainability report by Nielson suggesting that “73% of millennials are willing to spend more on a product if it comes from an ethical or sustainable brand.” A growing body of empirical work surveys consumers’ perspectives relating to slow fashion (de Lira and da Costa, 2022; de Oliveira et al., 2022), as well as those from producers and related stakeholders (Chhabra et al., 2022; Sellitto et al., 2022; Hall, 2018). Sun et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The anti-consumption concept described in the literature encompasses several different forms of renunciation of consumption. Voluntary simplicity (e.g., Alexander and Ussher 2012; García de Frutos, Ortega-Egea, and Martínez-del-Río 2018; Hüttel, Balderjahn, and Hoffmann 2020; Lasarov et al 2019; Seegebarth et al 2016), frugality (e.g., Lastovicka et al 1999), and slow consumption (e.g., slow fashion; Chhabra, Sindhi, and Nandy 2022; Ertekin and Atik 2015) are examples of these. Armstrong Soule and Sekhon (2022), for example, have demonstrated that not just environmental concern, but also the prospect of making this less consumption style prominent in the social context via status symbols, might inspire consumers to engage in anti-consumption behavior.…”
Section: Background and Hypotheses Developmentmentioning
confidence: 99%
“…In addition to reducing environmental impact, sustainable practices in Muslim fashion align with Islamic values, emphasizing responsible stewardship of the Earth. The concept of slow fashion [67,[75][76][77], promoting quality over trends, holds significance, and sustainability extends throughout the supply chain, emphasizing ethical sourcing and fair labor practices. This sustainability journey in Muslim fashion is not only about environmental responsibility but also aligns with the broader goals of promoting modesty, simplicity, and mindful consumption.…”
Section: Cluster 1: Sustainable Fashion and Circular Economymentioning
confidence: 99%